Mental health symptoms and associated factors among primary healthcare workers in China during the post-pandemic era - Liu, Difei; Zhou, Yuhe; Tao, Xubowen; Cheng, Yutong; Tao, Rui (Frontiers in Public Health, 2024)
The impact of the COVID-19 pandemic on mental health among healthcare workers has been widely reported during the initial and ongoing phases of the COVID-19 pandemic. Yet, little remains known about the mental health status of primary healthcare workers in China during the postpandemic era.A cross-sectional study was conducted between March 1, 2023, and May 31, 2023 in Anhui China. A total of 13,530 primary healthcare workers were recruited. Multiple logistic regression was used to identify potential factors associated with the incidence of depression and anxiety among primary healthcare workers.The prevalence of depression and anxiety among primary healthcare workers was 50.7% and 26.4%, respectively. Multiple logistic regression revealed that female gender (OR=1.345, 95%CI=1.222-1.479), being divorced or widowed (OR=1.432, 95%CI=1.128-1.817), being a nurse (OR=1.250, 95%CI=1.126-1.388), and working more than 8 hours per day (OR=1.710, 95%CI=1.583-1.846) were significantly associated with depression. A higher risk of anxiety among primary healthcare workers was associated with female gender (OR=1.338, 95%CI=1.198-1.494), being divorced or widowed (OR=1.373, 95%CI=1.056-1.770), being a nurse (OR=1.139, 95%CI=1.013-1.282), and working more than 8 hours per day (OR=1.638, 95%CI=1.497-1.794). Better monthly income, more than 21 years of working experience and without experience of workplace violence were protective factors against depression and anxiety during the post-pandemic era.Depressive symptoms are more common among primary healthcare workers in China during the post-pandemic era. Female gender, being divorced or widowed, being a nurse, working years, working seniority, monthly income, and experience of workplace violence were identified as associated factors.Targeted intervention is needed when developing strategies to reduce depression and improve primary healthcare workers' wellness and mental health.